TA’LIK TALAK DAN PERJANJIAN PERKAWINAN MENURUT FIKIH DAN KOMPILASI HUKUM ISLAM (ANALISIS PERBANDINGAN) - Nasaruddin, Nasaruddin (Hunafa: Jurnal Studia Islamika, 2007)
In Islam, marriage is sacred. Thus, the procedures of a marriage and of a divorce are arranged in Islam. One of the Islamic regulations on divorce is  ta’lik talak. Ta’lik talak in Islamic law is a marital contract declared by a husband in marriage through which a divorce will occur when the husband breaks the contract. In the Compilation of Islamic Law in Indonesia, we also find the so-called marital contract that has some similarities and differences from ta’lik talak. Ta’lik talak and marital contract can be done and can be a reason for executing a divorce when it is violated by the husband. However, ta’lik talak cannot be canceled as long as the marriage is intact. This is not the case with the marital contract where it can be canceled based on the agreement of the two (husband and wife), in spite of their intact marriage. Kata Kunci: Ta’lik talak, fikih, perjanjian perkawinan, Kompilasi   Hukum Islam